2019
DOI: 10.1111/anu.12985
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary protein level on growth performance, digestibility and activity of immunity‐related enzymes of leopard coral grouper,Plectropomus leopardus(Lacépède, 1802)

Abstract: An 8‐week feeding trial was conducted to assess the interaction between dietary protein levels and fish growth, digestibility and activity of immunity‐related enzymes of Plectropomus leopardus. Five diets with different protein levels (400 g/kg, 450 g/kg, 500 g/kg, 550 g/kg and 600 g/kg protein) were designed. P. leopardus fed with 500 g/kg, 550 g/kg and 600 g/kg dietary protein, showed higher weight gain rates than fish fed 400 g/kg and 450 g/kg dietary protein. Ingestion rate in fish fed with 500 g/kg dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The amylase enzyme activity in Nile tilapia will increase along with the increased starch content in the diet (Fitriliyani, 2011). A similar condition was also found in Trachinotus ovatus, Larmichthys crocea dan Plectropomus leopardu (Zhou et al, 2015;Zhou et al, 2016;Xia et al, 2019). Meanwhile, the lowest lipase enzyme activity was obtained from the TJt15%, TJt30%, and TJh30% treatments.…”
Section: Discussionsupporting
confidence: 79%
“…The amylase enzyme activity in Nile tilapia will increase along with the increased starch content in the diet (Fitriliyani, 2011). A similar condition was also found in Trachinotus ovatus, Larmichthys crocea dan Plectropomus leopardu (Zhou et al, 2015;Zhou et al, 2016;Xia et al, 2019). Meanwhile, the lowest lipase enzyme activity was obtained from the TJt15%, TJt30%, and TJh30% treatments.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, prices of red leopard coral grouper are significantly higher than those of the black fish, particularly in Chinese markets which showed the different possibility for the environmental and economic values for different body color fishes. Multiple factors influence the body color of leopard coral groupers, including climate change (Pratchett et al, 2017), temperature (Lutfiyah et al, 2019), salinity (Setiawati et al, 2017), and diet (Xia et al, 2019). Recently, the P. leopardus genome has been published, providing a basis for further chances of the intrinsic mechanism underlying body color variation and adaptation (Yang et al, 2020;Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of highly qualified aquafeed is essential to support this growth, yet nutrition and feed studies in this fish species are still quite limited. It has only been reported that juvenile coral trout require a dietary crude protein content of 50% for optimum growth (Xia et al, 2020). Compared with other grouper species, coral trout have a slower feeding process and relatively lower feed utilization (Giri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%